An Inspector Calls: Angus Mowat and Ontario’s Rural Libraries, 1937-40 - Bruce, Lorne (Ontario History, 2014)
Angus McGill Mowat was an inspirational voice for public library work during the Great Depression. In 1937, after he became Inspector of Public Libraries in the Ontario Department of Education, he helped revive spirits and raise service ambitions in smaller rural libraries. Building on the “modern library” concept popularized after the First World War, he re-energized trustees, librarians, and library workers with hundreds of visits to promote local efforts before 1939. His inspections encompassed the advisement of trustees on management and financial processes; the promotion of librarianship and staff training; the improvement of collections and services for adults and children; the reorganization of functional building space; the formation of county systems; and support for new public school curriculum reading reforms. Although warfare interrupted his work, Mowat’s wide-ranging inspection method brought renewed optimism and laid the groundwork for genuine progress in the provincial public library system after 1945.